Identifikasi Sakarin Dalam Sediaan Jamu Instan Beras Kencur Yang Beredar Di Pasar Gede Kota - Lutfi Indah Irmayanti; Danang Raharjo; Desy Ayu Irma Permatasari (Jurnal Medika Nusantara, 2023)
Saccharin is a synthetic chemical substance that is classified as a food or beverage additive. Excessive consumption of saccharin can cause side effects, including migraines and headaches, memory loss, confusion, insomnia, irritation, asthma, hypertension, diarrhea, stomach pain, allergies, impotence and sexual disorders, baldness, and brain and bladder cancer. The purpose of this study was to identify saccharin in beras kencur instant herbal preparations circulating in Pasar Gede, Surakarta. This research was conducted to determine the content of saccharin in instant herbal medicine using the color reaction method, Thin Layer Chromatography (TLC) and FTIR Spectroscopy. This research is an experimental descriptive research. The results of this study were 10 samples of instant herbal beras kencur MF, JM, SPA, IE, MR, BK, SP, BC, AG on the color reaction test, the negative TLC test contained saccharin. The FTIR spectral profile contains functional groups in the standard saccharin N-H (Stretching) secondary amine, C-H aromatic, C=O (stretching) carbonyl, C=C (stretching) cyclic aromatic, S=O sulfoksida, C-N (stretching) amine, C-H (bending) 1,2- substituted benzene (ortho) with wave numbers respectively 3402.68 cm-1, 3093.74 cm-1, 1718.84 cm-1, 1592.92 cm-1, 1358.84 cm-1, 1054.60 cm-1, 758.43 cm-1 which is in accordance with the literature. From the results of the analysis, it can be concluded that of the 10 samples of instant herbal medicine, beras kencur that was examined tested negative for the artificial sweetener saccharin. This shows that the beras kencur instant herbal medicine in market is safe for public